Avaliação do uso de sistema de educação à distância no ensino presencial - Carvalho, Fabrício Lopes de Souza (2008)
The use of information technology and its tools had a significant increase in the last decade, especially by the dissemination of information and communication technologies that have become part of our daily life. Despite this fact, most institutions still follow the traditional teaching methods. In the other hand, a teaching methodology known as Online Distance Education is starting to spread as a distinct teaching method, nevertheless there are a few studies about it. The collaborative environments and the Learning Management Systems (LMS), with all their tools, are beginning to be seen as powerful resources in education, not only as distance methods, but also as facilitators of the traditional teaching. This study has focused in the development of the LMS Moodle, with the objective of using it as a Blended Learning system, in Undergraduate and Graduate Degree in Production Engineering at Federal University Fluminense (UFF) and Information Systems Undergraduate at Paraíso University. A case study was conducted, about the difficulties encountered in this development and use, about tools, resources and about the feedback from students and teachers.